Long-life electrochemical supercapacitor based on a novel hierarchically carbon foam templated carbon nanotube electrode. (15th May 2018) - Dang, Alei; Li, Tiehu; Xiong, Chuanyin; Zhao, Tingkai; Shang, Yudong; Liu, Heguang; Chen, Xudong; Li, Hao; Zhuang, Qiang; Zhang, Shengzhao
Abstract: In this work, a long-life and high-performance electrode material is successfully fabricated by the incorporation of carbon nanotube (CNT) with different length using chemical vapor deposition (CVD) on a hierarchically three dimensional (3D) carbon foam (CF), which is obtained from the mesophase pitch. The morphology, composition, and electrochemical performance of the as-prepared composites are characterized using the scanning electron microscope (SEM), Raman spectroscopy, X-ray diffraction (XRD) patterns, cyclic voltammetry, and galvanostatic charge/discharge cycling techniques. Characterizations suggest that this resultant CF/CNT-50 electrode material has a good cycling stability with capacitance retention of 96.5% even after 10000 cycles. Moreover, it shows a high mass capacitance of 227.5 F/g based on the resultant electrode materials, higher energy density of 28 Wh kg −1 and power density of 3700 W kg −1 at a current density 2 A g −1 and also excellent charge/discharge rate. These measured charge storage properties make the proposed hybrid materials excellent electrode material candidates for high performance supercapacitors. Highlights: A hierarchically three dimensional (3D) structure composites was fabricated. Electro-active CNT on the surface of CF prepared in an innovative method. Excellent specific capacitance of CF/CNT-50 composites 227.5 F/g was obtained. Maintained the 96.5% of its initial capacitance after 10000 cycle test.